2017
DOI: 10.1016/j.ijrobp.2017.06.865
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Extent of Resection in Glioblastoma: Analysis from a Large Database

Abstract: Hemangiopericytomas are rare central nervous system (CNS) tumors. We sought to investigate existing clinical management strategies and overall survival (OS) among patients with hemangiopericytomas arising from the CNS. Materials/Methods: All patients diagnosed with CNS hemangiopericytoma from 2004-2014 in the National Cancer Database were included. Clinical and treatment-related characteristics were recorded and analyzed for an association with OS following diagnosis using univariable and multivariable analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…However, their data cannot differentiate between near-total resection and a lesser EOR, with a possible survival benefit of near-total resections. 26 In contrast, Sanai et al showed that subtotal tumor resection can impact OS in patients with a newly diagnosed GBM. 9 This is in line with the recent systematic review and meta-analysis of Brown et al that provides the evidence that resection < 95% improved OS compared with biopsy alone.…”
Section: Discussionmentioning
confidence: 97%
“…However, their data cannot differentiate between near-total resection and a lesser EOR, with a possible survival benefit of near-total resections. 26 In contrast, Sanai et al showed that subtotal tumor resection can impact OS in patients with a newly diagnosed GBM. 9 This is in line with the recent systematic review and meta-analysis of Brown et al that provides the evidence that resection < 95% improved OS compared with biopsy alone.…”
Section: Discussionmentioning
confidence: 97%
“…The literature has explored a number of aspects of the treatment of HGG. In terms of surgery, it is advised that a maximal safe resection (MSR) should be performed if benefits outweigh risks …”
Section: Discussionmentioning
confidence: 99%
“…Surgery for high-grade gliomas has the goal of maximum safe resection [49], with prognosis improvement, or at least partial resection or stereotactic biopsy to define histology, as well as molecular markers to drive treatment. Many strategies have been tested to reach maximum safe resection, such as awake surgery, intraoperative magnetic resonance [50], 5-aminolevulinic acid (5-ALA) guide surgery [48], and other techniques that require expertise and facilities to deal with these demands.…”
Section: High-grade Gliomasmentioning
confidence: 99%